فاعلية دورات التدريب المهني للمعلمين من وجهة نظر الموجهين التربويين _دراسة ميدانية على عينة في مدارس الحلقة الأولى في محافظة دمشق_ - المقطرن, سوزان; صبوح, نسرين (Latakia University Journal - Arts and Humanities Sciences Series, 2016)
The research aims to: identify the importance of vocational training for teachers and steps as courses method of educational guidance methods in the province of Damascus, and from the standpoint of supervisors, and adopted Find descriptive analytical approach to reach specific goals, and the original community of all supervisors working in the breeding Damascus Directorate of number (44) is directed and targeted educational been accredited as a sample for research, applied questionnaire them as a tool head of research.The results showed: there are statistically significant differences at the level of significance (0,05> = a) between the mean scores of the views of supervisors in the effectiveness of vocational training for teachers courses by sex variable in favor of males, and there are no differences between the mean scores of the views of supervisors in the effectiveness of courses vocational training for teachers as a variable in the educational experience.هدف البحث تعرف أهمية دورات التدريب المهني للمعلم وخطواتها بوصفها أسلوباً من أساليب التوجيه التربوي في محافظة دمشق, من وجهة نظر الموجهين التربويين, إذ اعتمد البحث المنهج الوصفي للتوصل إلى الأهداف المحددة, وتكون المجتمع الأصلي من جميع الموجهين التربويين العاملين في مديرية تربية دمشق والبالغ عددهم( 44) موجهاً وموجهة تربوية تم اعتمادهم كعينة للبحث, طبقت الاستبانة عليهم كأداة رئيسة للبحث.دلت النتائج على: وجود فروق ذات دلالة إحصائية عند مستوى دلالة(0,05>=a) بين متوسطات درجات آراء الموجهين التربويين في فاعلية دورات التدريب المهني للمعلمين حسب متغير الجنس لصالح الذكور, ولم تُظهر النتائج فروقاً دالة بين متوسطات درجات آراء الموجهين التربويين في فاعلية دورات التدريب المهني للمعلمين حسب متغير الخبرة في التربوي.